Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.5194/hess-21-183-2017
|View full text |Cite
|
Sign up to set email alerts
|

Effects of land use/land cover and climate changes on surface runoff in a semi-humid and semi-arid transition zone in northwest China

Abstract: Abstract. Water resources, which are considerably affected by land use/land cover (LULC) and climate changes, are a key limiting factor in highly vulnerable ecosystems in arid and semi-arid regions. The impacts of LULC and climate changes on water resources must be assessed in these areas. However, conflicting results regarding the effects of LULC and climate changes on runoff have been reported in relatively large basins, such as the Jinghe River basin (JRB), which is a typical catchment (> 45 000 km 2 ) loca… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
77
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 170 publications
(94 citation statements)
references
References 78 publications
7
77
2
Order By: Relevance
“…Models like the Soil and Water Assessment Tools (SWAT), which have the advantages of flexible scenario settings and the ability to detect spatial variations, can quantify the individual impacts of land‐use changes under otherwise identical conditions (Li, Liu, Zhang, & Zheng, ). SWAT has been applied to and shown to perform well in various regions of the world (Gassman, Reyes, Green, & Arnold, ), including China's Loess Plateau (Xu, Fu, & He, ; Yin, He, Xiong, & Qiu, ).…”
Section: Introductionmentioning
confidence: 99%
“…Models like the Soil and Water Assessment Tools (SWAT), which have the advantages of flexible scenario settings and the ability to detect spatial variations, can quantify the individual impacts of land‐use changes under otherwise identical conditions (Li, Liu, Zhang, & Zheng, ). SWAT has been applied to and shown to perform well in various regions of the world (Gassman, Reyes, Green, & Arnold, ), including China's Loess Plateau (Xu, Fu, & He, ; Yin, He, Xiong, & Qiu, ).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, LUCC was found to influence the hydrological cycle including precipitation, evapotranspiration, infiltration and runoff [37]. Evapotranspiration decreased rapidly from 1980 to 1998, and then decreased slightly from 1999 to 2015 ( Figure S9a).…”
Section: Discussionmentioning
confidence: 99%
“…The modeled streamflow represents the impacts of constant LUCC data for 1980 and 2005, whereas the observations are based on dynamic LUCC data, which could explain the discrepancy. Yin et al (2017) studied the impact of LUCC on the streamflow in the Jinghe River basin, which is the largest tributary of the Wei River basin, and found that the streamflow was increasingly influenced by LUCC; it contributed to 44 % of the streamflow changes between the 1980s and the 1990s and 71 % of the streamflow changes between the 1990s and the 2000s. At the same time, different land use types hydrologically respond differently, even to the same meteorological forcings; i.e., rainfall intensity was of great importance in influencing the hydrological process in semi-dry and semi-humid regions (Lacombe et al, 2008;Wang, 2014).…”
Section: Impact Of the Observed Lucc On Streamflowmentioning
confidence: 99%